Green house gas mitigation and headline targets of Europe 2020 strategy - Lazányi, János (Applied Studies in Agribusiness and Commerce, 2010)
Climate change is considered as one of the biggest challenges of XXI century and global action is needed to mitigate greenhouse gases (GHG) and adapt to changing water levels and temperatures, which affect food supply and ecosystem integrity. Climate change will have significant economic and social impacts in many regions of EU and sectors like agriculture is considered to bear greater adverse affects. Less developed regions and certain sections of society (the elderly and/or low-income households) are expected to suffer more from climate change. Climate change policy of EU, adopted in December 2008, includes ambitious targets for 2020. The policy is focused on a sustainable future with an energy-efficient economy by (i) cutting greenhouse gases by 20% (30% if international agreement is reached), (ii) reducing energy consumption by 20% through increased energy efficiency and iii) meeting 20% of energy needs from renewable sources. In the frame of the headline targets of Europe 2020 Strategy, this paper discusses most important greenhouse gas-emitting activities in agriculture, emphasizes the importance structural changes through the modernisation of infrastructure particularly in developing regions of EU and calls for enhancing the competitiveness of economy to promote energy efficiency.